2021
DOI: 10.1002/hpm.3151
|View full text |Cite
|
Sign up to set email alerts
|

‘We are not aware of notification of tuberculosis’: A mixed‐methods study among private practitioners from western India

Abstract: Background Implementing the Standards for tuberculosis care in India (STCI) guidelines in the private sector is vital. This study attempted to estimate the knowledge and practices regarding STCI guidelines among private practitioners and to explore the reasons and solutions for low tuberculosis (TB) notification rates. Methods We conducted a cross‐sectional study for assessing the knowledge and practices of the STCI guidelines among 100 full‐time allopathic private practitioners in Bhavnagar (in western part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Most of our participants preferred messaging applications such as SMS and WhatsApp group chat as a way to report TB cases; this is in line with findings from other studies. 18 , 25 Additionally, around half of our participants also mentioned that in the last 6 months, they were not visited by CHCs officers for TB case reporting.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most of our participants preferred messaging applications such as SMS and WhatsApp group chat as a way to report TB cases; this is in line with findings from other studies. 18 , 25 Additionally, around half of our participants also mentioned that in the last 6 months, they were not visited by CHCs officers for TB case reporting.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, CHCs officers should monitor TB case recording and reporting from private providers regularly. 25 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…According to the International Standards for Tuberculosis Care (ISTC) and the Vietnam Ministry of Health’s guidelines for TB diagnosis and treatment, CXR findings alone are unreliable for diagnosing TB, and sputum examination must be performed when CXR findings are suggestive [ 15 , 17 ]. In other studies, CXR alone was the preferred investigations for the diagnosis of TB in 45,4%–68% of the participants [ 18 21 ]. This tendency could either be due to the lack of knowledge among private practitioners regarding the availability/reliability of sputum smear in TB diagnosis, or to the fact that the CXR/CT scan is faster and more convenient, making it more suitable for the practice in private sector, where private providers are frequently under pressure to provide immediate results to their clients.…”
Section: Discussionmentioning
confidence: 99%
“…1 A study conducted in western India indicated that private practitioners are still slow in raising TB notifications. 54 Collaboration within private practitioners and community pharmacy is expected to raise TB case notification. Community pharmacy personnel can screen pharmacy visitors for TB signs and symptoms and refer presumptive TB patients to healthcare facilities or community healthcare centers for further examination as has been done in India and Pakistan 13 , 15 to enhance the notification of TB cases.…”
Section: Discussionmentioning
confidence: 99%